Experiences of Urinary Incontinence Management in Older Women: A Qualitative Study - Javanmardifard, Sorur; Gheibizadeh, Mahin; Shirazi, Fatemeh; Zarea, Kourosh; Ghodsbin, Fariba (Frontiers in Public Health, 2022)
Introduction Older women have various experiences regarding the management of urinary incontinence depending on the societies they live in and their cultural backgrounds. The present study aimed to determine older women's experiences in urinary incontinence management. Methods The present qualitative study employed a conventional content analysis approach and was conducted in Iran from 2019 to 2020. In this research, the data were collected through face-to-face unstructured in-depth interviews with 22 older women suffering from urinary incontinence selected via purposeful sampling. The interviews were continued until reaching the data saturation point. Data analysis was performed simultaneously with data collection. The interviews were recorded, transcribed, and analyzed through Graneheim and Lundman style content analysis, and data management was done using the MAXQDA software. In order to achieve the accuracy and validity of the study, the Four-Dimensions Criteria (FDC) by Lincoln and Guba, namely credibility, dependability, conformability, and transformability, were considered and used. Results This study was conducted on 22 older women suffering from urinary incontinence with the mean age of 66.54 ± 5.76 years. The acquired data were put in four main categories of “resilience” with three subcategories, “change in lifestyle” with six subcategories, “attempt for treatment of the condition” with three subcategories, and “receiving support” with two subcategories. Conclusion The study results indicated that the older women suffering from urinary incontinence were resilient against the condition, had changed their lifestyles to manage the condition, and sought treatment. In addition, receiving support from the family and the society played a significant role in the follow-up and management of the condition. The present study findings can help healthcare team members focus on urinary incontinence, design care programs for older women with this condition, and improve their quality of life. Furthermore, focusing on young and middle-aged women's health, providing them with the necessary training for taking care of the genitourinary system, and raising their awareness for preventing urinary incontinence during old ages can be helpful. Moreover, increasing the healthcare team's sensitivity and following the patients up can help diagnose, manage, and treat the condition before exerting adverse impacts on their quality of life.